PET of EGFR with 64Cu‐cetuximab‐F(ab′)2 in mice with head and neck squamous cell carcinoma xenografts. (4th August 2015) - van Dijk, Laura K.; Yim, Cheng‐Bin; Franssen, Gerben M.; Kaanders, Johannes H. A. M.; Rajander, Johan; Solin, Olof; Grönroos, Tove J.; Boerman, Otto C.; Bussink, Johan
Abstract : Overexpression of the epidermal growth factor receptor (EGFR) is linked to an adverse outcome in various solid tumors. Cetuximab is an EGFR inhibitor, which in combination with radiotherapy improves locoregional control and survival in a subgroup of patients with head and neck squamous cell carcinomas (HNSCCs). The aim of this study was to develop and characterize an EGFR‐directed PET tracer, 64 Cu‐cetuximab‐F(ab′)2, to determine the systemic accessibility of EGFR. Mice with HNSCC xenografts, UT‐SCC‐8 ( n  = 6) or UT‐SCC‐45 ( n  = 6), were imaged 24 h post injection with 64 Cu‐NODAGA‐cetuximab‐F(ab′)2 using PET/CT. One mouse for each tumor model was co‐injected with excess unlabeled cetuximab 3 days before radiotracer injection to determine non‐EGFR‐mediated uptake. Ex vivo biodistribution of the tracer was determined and tumors were analyzed by autoradiography and immunohistochemistry. The SUVmax of UT‐SCC‐8 tumors was higher than that of UT‐SCC‐45: 1.5 ± 1.0 and 0.8 ± 0.2 ( p  < 0.05), respectively. SUVmax after in vivo blocking of EGFR with cetuximab was 0.4. Immunohistochemistry showed that UT‐SCC‐8 had a significantly higher EGFR expression than UT‐SCC‐45: 0.50 ± 0.19 versus 0.12 ± 0.08 ( p  < 0.005), respectively. Autoradiography indicated that 64 Cu‐cetuximab‐F(ab′)2 uptake correlated with EGFR expression in both tumors: r  = 0.86 ± 0.06 (UT‐SCC‐8) and 0.90 ± 0.06 (UT‐SCC‐45). 64 Cu‐cetuxmab‐F(ab′)2 is a promising PET tracer to determine expression of EGFR in vivo . Clinically, this tracer has the potential to be used to determine cetuximab targeting of tumors and possibly to non‐invasively monitor the response to EGFR‐inhibitor treatment. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : 64 Cu‐NODAGA‐cetuxmab‐F(ab′)2 is a promising PET tracer to determine expression of EGFR in vivo as seen in these HNSCC xenograft models with different EGFR expression levels.